Surveying the Future of Computer and Data Science Education - Prospects and Pitfalls of Generative AI on Pedagogical Approaches - Araújo, Vitor Meneghetti Ugulino de; Pinto, Pedro Henrique Ramos; Ferreira Junior, Cleydson de Souza; Marques, Maria Jullyanna Ferreira; Goulart, Lutero Lima; Aguiar, Gabriel Silva; Lira, Paloma Duarte de; Mendes, Samuel José Fernandes (Anais do Workshop sobre Educação em Computação (WEI), 2024)
This study investigates the role of generative Artificial Intelligence (AI), like ChatGPT and other Large Language Models (LLMs), on learning strategies among computer and data science students at the Center for Informatics, University of Paraíba (CI/UFPB), Brazil. Analyzing 178 responses, the research highlights a significant engagement with LLMs and discovers a moderate correlation between students' LLM knowledge and their use of metacognitive learning strategies. Additionally, findings suggest a decrease in dysfunctional learning strategies with academic progression. The study reveals AI's potential to improve personalized learning while emphasizing the need for educational adjustments to avoid overreliance on AI.